Knowledge, Moral Claims and the Exercise of Power in Global Health - Jeremy Shiffman (Kerman University of Medical Sciences, 2014)
A number of individuals and organizations have considerable influence over the selection of global health priorities and strategies. For some that influence derives from control over financial resources. For others it comes from expertise and claims to moral authority-what can be termed, respectively, epistemic and normative power. In contrast to financial power, we commonly take for granted that epistemic and normative forms of power are legitimate. I argue that we should not; rather we should investigate the origins of these forms of power, and consider under what circumstances they are justly derived.